Early apoptotic features of K562 cell death induced by 5-aminolaevulinic acid-based photodynamic therapy - Kuzelová, K; Grebenová, D; Pluskalová, M; Marinov, I; Hrkal, Z (Journal of photochemistry and photobiology. B, Biology, 2004)
5-Aminolaevulinic acid-based photodynamic therapy (ALA-PDT) is used to eliminate cancerous cells through photoactivation of endogenously formed protoporphyrin IX (PPIX) following the administration of PPIX precursor, 5-aminolaevulinic acid (ALA). We report on the kinetics of PPIX accumulation and the mechanism of cytotoxic effects of ALA-PDT studied in the chronic myelogenous leukaemia derived cell line K562. The PPIX distribution and, consequently, cytotoxic effects were found to be heterogenous. A subpopulation of K562 cells accumulating PPIX to a lesser extent exhibits only transient cell cycle arrest. A fraction of cells, probably those with higher PPIX accumulation, are irreversibly damaged by ALA-PDT. We detected several signs of an early apoptosis: lowering of Bcl-xL expression, decrease of the mitochondrial and plasma membrane potential, the cytochrome c release into the cytoplasm, and the unmasking of the mitochondrial antigen 7A6. However, late apoptotic events were lacking: neither caspase-3 activation nor DNA fragmentation occurred. Instead, rapidly progressing cell necrosis resulting from plasma membrane damage was observed. We suggest that the high level of the antiapoptotic heat-shock proteins HSP70 and HSP27 found by us in the K562 cells is responsible for the inhibition of the apoptotic process upstream of caspases activation.
Keywords: buněčné dělení; apoptóza; vztah mezi dávkou a účinkem léčiva; In Situ Nick-End Labeling; kyselina aminolevulová; Apoptosis; lidé; Photochemotherapy; Photosensitizing Agents; fotosenzibilizující látky; Dose-Response Relationship, Drug; koncové značení zlomů DNA in situ; K562 Cells; Aminolevulinic Acid; Cell Survival; viabilita buněk; buňky K562; Cell Division; fotochemoterapie; Humans